Evaluasi kebijakan integrasi angkutan pengumpan ke dalam sistem bus rapid transit: Studi pada Mikrotrans Jaklingko - Gary Ekatama Bangun; I Made Suwandi (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
This research discusses the evaluation of the Integration of Feeder Transport into the Bus Rapid Transit System in the small bus transport segment through Mikrotrans Jaklingko program, which is one of Transjakarta's services in the small bus segment in order to integrate feeder transport into the bus rapid transit system to provide good quality and affordable public transport services for the community, this program also aims to improve the operational pattern of public transportation in the small bus segment so that it meets the minimum service standards. With the CIPP evaluation model initiated by Stufflebeam, the research approach used is post-positivism with qualitative data collection. The results show that the policy of integrating feeder transport into the bus rapid transit system has been implemented in accordance with the rules contained in the DKI Jakarta Governor’s Regulation Number 96 of 2018. This can be seen from the integration that has reached the small bus transport segment through the Mikrotrans Jaklingko, but there are a number of obstacles to the implementation of the Mikrotrans Jaklingko in terms of Input which have an impact on other dimensions, Process and Product. There are several recommendations that can be given, including providing a special place for fleet storage, optimizing means of providing information, standardizing terms and conditions in the Decree, and also evaluating existing routes for the purpose of adjusting fleet numbers.